2011
DOI: 10.1021/bi200750k
|View full text |Cite
|
Sign up to set email alerts
|

Native-State Interconversion of a Metamorphic Protein Requires Global Unfolding

Abstract: Lymphotactin (Ltn) is a unique chemokine that under physiological solution conditions displays large-scale structural heterogeneity, defining a new category of ‘metamorphic proteins’. Previous Ltn studies have indicated that each form is required for proper function, but the mechanism of interconversion remains unknown. Here we have investigated the temperature dependence of kinetic rates associated with interconversion and unfolding by stopped-flow fluorescence to determine transition-state free energies. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
93
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(102 citation statements)
references
References 16 publications
7
93
2
Order By: Relevance
“…7 This restructuring is accompanied by changes in the overall distribution of electrostatic charges on the surface of XCL1 (Figure 1A–D). XCL1 mon contains 15 basic and six acidic residues (Figure 1E), resulting in a theoretical isoelectric point (pI) of 10.6.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 This restructuring is accompanied by changes in the overall distribution of electrostatic charges on the surface of XCL1 (Figure 1A–D). XCL1 mon contains 15 basic and six acidic residues (Figure 1E), resulting in a theoretical isoelectric point (pI) of 10.6.…”
Section: Resultsmentioning
confidence: 99%
“…4,6 The XCL1 dim conformation is an unrelated β -sandwich dimer that is responsible for binding to GAGs. 5 Both native state structures can be accessed through a dynamic equilibrium unfolding process, 7 designated as metamorphic interconversion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 Interconversion between these two folds involves a complete restructuring of the core residues. 5 Since the development of soft ionization techniques such as electrospray ionization (ESI) and nano-ESI (n-ESI), mass spectrometry (MS) has become a valuable tool for structural analysis of proteins and protein complexes, and methods have been established that can preserve solution topologies. 6−9 Furthermore, theoretical studies have suggested that major secondary structural features of proteins can be preserved during transfer into the gas phase under ESI conditions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Therefore, it is likely that the interconversion requires the complete unfolding and refolding, rather than a well-structured intermediate; this mechanistic hypothesis is consistent with the kinetic analyses of hLtn10/ hLtn40 interconversion and unfolding of the two species. 17 The hLtn system represents a remarkable example for how environmental properties, such as salt and temperature modulate protein stability through the interplay of electrostatics and hydrophobic interactions. 18−20 Prior to the solution of the NMR structure for hLtn40, 12 our molecular dynamics (MD) studies 21,22 focused on probing changes in structural stability of hLtn10 at the scale of tens of nanoseconds when temperature and salt concentration was varied separately.…”
Section: ■ Introductionmentioning
confidence: 99%